Religious thinking in children's short story published between 2012 and 2015 and its positive impact on children - Mohd, Farra Humairah; Nik Muhamad Affendi, Nik Rafidah; Hamzah, Nordiana; Baharum, Hasrina (Auricle Technologies, 2020)
This working paper discusses the religious thought in selected children’s short stories published between 2012 and 2015. The Panel of Assessor for Malaysia’s Premier Literary Award (HSPM) has expressed their disappointment with the mediocre quality of children’s short stories. Some believed that these short stories were written from the perspective of adult authors and did not satisfy the concept for children’s literature and child psychology. The present research adopts a qualitative approach of text analysis to identify and analyse whether the religious thoughts presented in each short story have a positive impact on the children or vice versa. This research seeks to determine whether the selected children’s short stories failed to provide good examples for their readers and that the authors failed to include child psychology and fulfil the literary concept for children in their writings. Scrutiny of the selected children’s short stories published between 2012 and 2015 showed that presented using the teaching elements based on the moral approach, preaching approach, and community approach in the Malay Methodology (Hashim Awang). Even though the authors included religious thought in the short stories to impart positive influence on the children, they failed to present the thought comprehensively because they did not adopt the concept of children’s literature and child psychology. Hence, this research seeks to identify and analyse the religious thought presented by the authors by scrutinising its positive influence on the readers, particularly children. This research adopts the model for children’s needs (an integration of Maslow’s theory with the Malay Methodology theory).